Styl i stylistyka w kształceniu językowym - Nocoń, Jolanta (Stylistyka, 2020)
The article attempts to define the place of style and stylistics in the process of teaching Polish as the first language. The paper takes as its reference the current Polish language curriculum, adopting the assumption that curriculum documents present the typical approach to style and stylistics found in Polish language didactics. Issues of style and stylistics are introduced in education in association with the development of productive skills (speaking and writing) and receptive skills (reading and listening). The analysis of curriculum guidelines has shown five aspect of style/stylistics competence that are concentrated on in the classroom: text reception on the level of stylistic and linguistic means, on the level of text style and functional style, intentional use of stylistic and linguistic means in texts produced by pupils, intentional construction of texts with certain features of style. The author concluded that style ought to be treated as an integrating, organizing category in the development of receptive and productive skills. The knowledge of style and specific stylistic and linguistic skills on the one hand enables characterising the language of texts read and listened to by pupils in order to grasp the gist of the message, and on the other allow them to choose linguistic measures to produce their own verbal and written texts in an intentional, purposeful manner. The curriculum under analysis does go in this direction, albeit quite incoherently and accidentally. The main problem lies in the blurred categorisation of related terms: style – variant – language.